HyperMap: A system to map the web - Ralha, C.G.; Ralha, J.C.L. (Journal of Digital Information Management, 2006)
This paper presents the HyperMap system which dynamically structures information on the Web. The system is based on a framework resulting from multidisciplinary research, which is briefly discussed. This paper focuses work done to develop a new generation of computational tools able to support the extraction and the discovery of useful information on the Web, becoming agents of innovation and development.
Keywords: Concept mapping; Hyper space; Information extraction; Knowledge discovery; Semantic web; Web knowledge discovery; Web navigation